ответ:Sin^6α-cos^6α-(3/4)*cos²2α+(3/4)*sin²α sin^6α-cos^6α-(3/4)*cos²α+(3/4)*sin²α= -(cos^6α-sin^6α)-(3/4)(cos²α-sin²α)= -(cos²α-sin²α)(cos^4α+sin²α*cos²α+sin^4α) -3/4(cos²α-sin²α)= -(cos²α-sin²α)(cos^4α+sin²α*cos²α+sin^4α -3/4)= -cos2α((cos²α+sin²α)²-cos²α*sin²α -3/4)= - cos2α(1-(1/4)*sin²2α -3/4)= - cos2α(1/4-(1/4)*sin²2α)= - (1/4)cos2α*(1-sin²2α) = - (1/4)cos2α*cos²2α= - (1/4)cos³2α .
Подробнее – на Otvet.Ws – https://otvet.ws/questions/4864874-pomogite-pozhaluista-sin6a-cos6a-34cos2a34sin2a.h
1)-8, 2) 7
Пошаговое объяснение:
Т.к. квадрат числа всегда больше или равен нулю, то его наименьшее значение равно нулю.
При х=0: -8=0-8=-8
При х=0: 7+ =7+0=7